Crowdsourcing the curriculum: Information literacy instruction in first-year writing. Issue 2 (3rd June 2014) - White-Farnham, Jamie; Caffrey Gardner, Carolyn
Abstract : Purpose: – The purpose of this article is to describe the rationale, process and results of an integrated curricular intervention for information literacy instruction in a first-year writing program. Design/methodology/approach: – The information literacy coordinator collaborated with writing instructors and the Writing Program Administrator on the initial design of information literacy outcomes. The librarian and instructors created a modular curriculum with multiple lessons and activities aligned to each outcome. The curriculum was housed in the course management system for easy updating and distribution. Finally, instructors taught the embedded information literacy activities for two semesters and measured student improvement through a pre-/post-survey and a rubric-based assessment of students' citation and documentation. Findings: – Students saw significant gains over the course of the semester in their ability to use Boolean operators, identify the purpose of sources and understand citation styles. As a related and valuable measure, writing program assessment results showed an improvement in students' performance in citation and documentation in researched writing assignments after a one-year implementation of the intervention. Writing instructors reported an increased awareness of information literacy pedagogy and intentionality in their teaching. Finally, the librarian was able to leverage this collaboration to highlight the teaching roles of librarians beyond the one-shot. Originality/value: – Well-known temporal and logistical limits exist in regard to embedded, one-shot and multi-shot approaches to information literacy. The latter two are especially unsustainable when implemented at scale, such as within a first-year writing program that serves hundreds or thousands of students each semester. This study documents a faculty development approach in which writing instructors integrate information literacy (IL) into their own instruction. This offers a model that makes explicit IL processes and skills to writing instructors, results in high student performance and allows especially the small college librarian to manage his/her other strategic information literacy partnerships.